Musculoskeletal ultrasound in pediatric rheumatology - Özçakar Levent; Demirkaya Erkan; Tok Fatih (BMC, 2011)
Abstract Although musculoskeletal ultrasound (MSUS) has emerged as an indispensible tool among physicians involved in musculoskeletal medicine in the last two decades, only recently has it become more attractive to pediatric rheumatologists. Thereafter, the use of MSUS in pediatric rheumatology has started to increase. Yet, an ever-growing body of literature shows parity and even superiority of MSUS when compared to physical examination and other imaging modalities. MSUS is suitable for examination of children of all ages and it has certain advantages over other imaging modalities; as it is cheaper, mobile, instantly accessible bedside, easy to combine with clinical assessment (interactivity) and non-invasive. It does not require sedation, which facilitates repetitive examinations. Assessment of multiple locations is possible during the same session. Agitation is rarely a problem and small children can be seated in their parents' lap or they can even play while being examined.